2018
DOI: 10.18868/sher5j.05.01213.04
|View full text |Cite
|
Sign up to set email alerts
|

Academic Emotions And Performance of the Senior High School Students: Basis for Intervention Program

Abstract: Emotions are ever-present in academic settings and can significantly influence learning and achievement. Since the classroom is an emotional place, students often experience emotions in school. This study determined the effect of academic emotions in academic settings such as attending class, studying lesson, and taking test/exam towards academic performance to find remedies and effective measures aim to yield an intervention program to improve the learning experience of the students. Descriptivecorrelational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Emotional experiences are ever-present in education, playing a fundamental role in the learning process, since they affect the motivation and performance of students (Destacamento, 2018;Pekrun, 2006). Therefore, its study in recent years has expanded, trying to cover, in addition to the emotions experienced by students (Lichtenfeld et al, 2012;Pekrun, 2006;Pekrun et al, 2017), the emotions experienced by teachers (Becker et al, 2014;Chen, 2019;Keller et al, 2014;Frenzel et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional experiences are ever-present in education, playing a fundamental role in the learning process, since they affect the motivation and performance of students (Destacamento, 2018;Pekrun, 2006). Therefore, its study in recent years has expanded, trying to cover, in addition to the emotions experienced by students (Lichtenfeld et al, 2012;Pekrun, 2006;Pekrun et al, 2017), the emotions experienced by teachers (Becker et al, 2014;Chen, 2019;Keller et al, 2014;Frenzel et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…he importance of emotions in education is widely acknowledged and a recurring study topic as emotions have been, amongst others, shown to be relevant for learning processes and achievement (Destacamento, 2018;Frenzel et al, 2016;Luo et al, 2019;Pekrun, 2006). For a long time, the research in this field has mainly focused on showing the antecedents and effects of students' emotions, especially test anxiety (Lichtenfeld et al, 2012;Pekrun et al, 2017;Pekrun, 2006).…”
mentioning
confidence: 99%
“…According to [ 3 ], emotional experiences are always present and meaningful. Emotions are very important in the teaching process [ 4 ], influencing students’ motivation and academic achievements, as they may feel excited while studying and be proud of their achievements, or they may have negative emotions, stemming from poor grades or boredom during lessons [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Damasio (2001) mostró que, por un lado, la separación entre emoción y razón es imposible y por el otro, que las emociones jugaban un papel muy importante en la toma de las decisiones. Por este motivo, la investigación sobre emociones en la educación en general (Destacamento, 2018;Pekrun et al, 2011) y en la educación 2021, Retos, 42, 434-442 © Copyright: Federación Española de Asociaciones de Docentes de Educación Física (FEADEF) ISSN: Edición impresa: 1579-1726. Edición Web: 1988-2041 física en particular (Fierro-Suero et al, 2020;Leisterer & Jekauc, 2019;Mujica, 2021;Mujica & Jiménez, 2021;Simonton & Garn, 2019) ha pasado a ser un tema frecuente de estudio en las últimas décadas.…”
Section: Introductionunclassified